Effect of heat treatment conditions on properties of carbon-fiber-based electromagnetic-wave-absorbing composites. Issue 4 (March 2019) - Ye, Wei; Sun, Qilong; Zhang, GuangYu
Abstract: Hybridization of carbon materials with magnetic metals and oxides has become a research hotspot in electromagnetic (EM) wave loss of reinforced materials. In this study, EM wave-absorbing composites were prepared by a one-step, high-temperature process using a polyacrylonitrile (PAN)-based pre-oxidized felt impregnated with a metal salt solution containing Fe, Co, and Ni. The structures, chemical compositions, and morphologies of the obtained composites were analyzed in detail. The carbon fiber (CF)/FeCoNi composites are composed of carbon fibers and Fe3 O4, NiFe2 O4, CoFe2 O4, and Ni3 Fe particles with magnetic loss properties. The magnetic particles are distributed uniformly along the axial direction of the fiber, and EM waves are reflected by multiple reflections in the fiber felt. In addition, the CF/FeCoNi composites exhibit excellent performances owing to the synergistic effect of electric loss and magnetic loss materials, and different wave-absorbing properties. The maximum reflection loss of CF/FeCoNi was − 30.62 dB at 11.74 GHz, and the absorption bandwidth with a reflection loss exceeding − 10 dB was 7.4 GHz (from 8.7 to 16.1 GHz) with 1 h of heat treatment at 650 °C. By adjusting the treatment temperature and time, composite materials can be obtained to serve as lightweight and high-performance EM wave-absorbing materials.